Access to Home Equity and Consumption: Evidence from a Policy Experiment - Agarwal, Sumit; Qian, Wenlan (The Review of Economics and Statistics, 2017)
Using unique consumer financial transactions of more than 56,000 consumers, we study the consumption response to a housing policy experiment in Singapore that resulted in a decrease in access to home equity. Using difference-in-differences analysis, we find a significant negative consumption response to the policy shock. Moreover, the consumption response is concentrated in credit card spending and is stronger among individuals with limited access to credit market or with a high precautionary saving motive. These results suggest that a decrease in access to home equity reduces the role of housing as a self-insurance mechanism for consumption smoothing.